EFFECT OF SALINE WATER ON GROWTH, CHEMICAL COMPOSITION AND MICROBIOLOGICAL SAFETY EVALUATION OF RADISH ETIOLATED SPROUTS - Amira Bondok; H. Abd El-Gawad; M. Abd El- Ghany; Mز Abdallah (Arab Universities Journal of Agricultural Sciences, 2019)
Egyptian radish sterilized seeds were sprouted for 3 days using tap and saline water NaCl 2000 ppm to study sprout characters, chemical composition, protein fraction and safety aspects such as microbiological examinations and biogenic amines were investigated at 3 days old. The results indicated that sterilized seeds increased sprout growth compared with non-sterilized. Seeds sprouting increased in protein content, moister, ash and fibers while carbohydrate, lipid content and energy decrease in etiolated sprouts. Using saline water and seeds sterilization for sprouting increased albumin, globulin and glutenin fractionation but decreased prolamin compared with sprouts produced with tap water and without seed sterilization.  Using sterilization by 2% calcium hypochlorite of seeds before sprouting led to decreasing in total bacterial count compared with non-sterile seeds sprouts, the same was in total coliform, total yeast and total fungi counts. The sprouts product which washed with saline water was contain total bacterial count less than which washed by tap water. All sprouts under investigation were free from feacal coliform and all examined pathogenic microorganism under investigation like Staph. aureus, B. cereus and Salmonella spp.  Use sterilized seeds for sprouting caused big decrement on biogenic amines content of radish sprout. Radish sprout contain biogenic amines but it is lower than previous ranges, sprouts can be considered a safe food and germination of seeds either use tap or saline water.